Optimizing the Integration of Employment Information Systems for Higher Education Institutions Graduates - Khairullaevna, Shoakhmedova Nozima; Gaibullaevna, Mannanova Shakhida; Mirabidovna, Yusupova Dilbar (European Journal of Life Safety and Stability (2660-9630), 2022)
One of the main problems of universities is the issue of monitoring the employment of graduates. The article provides information on the creation of a platform for the employment of university graduates in the digital economy, the development of a unified digital platform for the employment of graduates and the study of foreign experience in this area. The key factors contributing to the formation of young professionals are identified. The article describes the features of cooperation between an educational institution and employers: the features are analyzed, the results are described, and the prospects for cooperation are disclosed. Particular attention is paid to the analysis of professional and personal requirements for university graduates in the labor market.